THE EFFECTS OF TRANSFORMATION DURATION ON THE QUANTITY OF SWINE PATHOGENIC ESCHERICHIA COLI ISOLATE - Kalyana Lionita; I Gusti Ngurah Kade Mahardika; Anak Agung Sagung Kendran (Buletin Veteriner Udayana, 2025)
DNA transformation generally still utilizes commercial Escherichia coli bacteria, and the use of virulent pathogenic bacteria has never been reported. Utilizing virulent pathogenic bacteria can provide an advantage, as the product can be used as a vaccine against the genetic material in the plasmid and against the pathogenic bacteria itself. This study aims to determine how the transformation duration affects the number of swine Escherichia coli pathogenic isolates colonies. The samples of this study are swine Escherichia coli pathogenic isolates BPOS4 and E. coli BL21 (DE3) which were made into competent cells by calcium chloride heat shock method and then transformed with the different transformation of times using plasmid pGEX-2T+ASF A224L. The results showed that E. coli BL21 (DE3) and swine Escherichia coli pathogenic isolates BPOS4 had no significant effect on the quantity of colonies after transformation. Although statistically the effect was not significant, E. coli BL21(DE3) gave a higher colony count with an average of 62,4×105 CFU/100µL compared to E. coli BPOS4 of 33,45×105 CFU/100µL. The transformation time has no significant effect on the number of bacterial colonies after transformation, however, the best transformation time is shown by the treatment of 60 seconds with an average colony of 86,5×105 CFU/100µL. It can be concluded that the colonies of E. coli BL21 (DE3) and E. coli BPOS4 transformed with plasmid pGEX-2T+ASF A224L can grow optimally in 60 seconds. Further research can be conducted, such as developing Escherichia coli vaccines using pathogenic strains.